2023
DOI: 10.1177/17474930221143323
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Latin America: Systematic review of incidence, prevalence, and case-fatality in 1997–2021

Abstract: Background: Stroke is a major global cause of death and disability. Most strokes occur in populations of low-middle income (LMIC); therefore, the subsequent disease burden is greater than in populations of high-income countries. Few epidemiological data exist for stroke in Latin America, composed primarily of LMIC. Aims: To determine epidemiological measures of incidence, prevalence, and 1-month case-fatality for stroke in Latin America/Caribbean (LAC) during 1997-2021. Summary of review: A structured search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(98 reference statements)
0
7
0
Order By: Relevance
“…The search strategy followed the same parameters of our previous publication 8 . A modified search strategy of the Cochrane Stroke Group filtered by terms for Latin American and the Caribbean was used to identify studies that met the selection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…The search strategy followed the same parameters of our previous publication 8 . A modified search strategy of the Cochrane Stroke Group filtered by terms for Latin American and the Caribbean was used to identify studies that met the selection criteria.…”
Section: Methodsmentioning
confidence: 99%
“…International Journal of Stroke, 18 (6) sex, and admission blood pressure, while a lower risk was found in patients with the thalamic lacunar infarction. Furthermore, they found that END was associated with an unfavorable outcome, They concluded that high systolic blood pressure may be a potentially modifiable risk factor to prevent END, but this needs investigation in randomized controlled trials.…”
mentioning
confidence: 91%
“…Their conclusions are consistent with an epidemiological study from Sierra Leone which found stroke affected younger people and resulted in high rates of fatality and functional impairment relative to global averages. 5 Delfino et al 6 from South Africa also highlight the need for studies to better understand the burden of stroke, and how it varies, across South America.…”
mentioning
confidence: 99%
“…2,3 We have also recently published in this journal detailed analyses of stroke risk in various countries and continents including Africa, India, China, and South America. 47 Together these show major disparities in stroke incidence and mortality and worryingly upward trends in incidence in many LMICs, but more positively highlight how stroke risk could be reduced with environmental and cardiovascular risk factor initiatives.…”
mentioning
confidence: 98%